Dari Pasar Tradisional ke Pasar Modern: Perubahan Pasar Wonokromo menjadi Darmo Trade Center 2005-2019 - Afifah Nabila Firdausi; Nasution (Integrative Perspectives of Social and Science Journal, 2026)
This study entitled "From Traditional Market to Modern Market: The Transformation of Wonokromo Market into Darmo Trade Center, 2005–2019," examines the transformation of Wonokromo Market into Darmo Trade Center (DTC) and its impact on the socio-economic conditions of traders during the period of 2005–2019. The objectives of this research are to identify the background of the transformation of Wonokromo Market into Darmo Trade Center (DTC), analyze the transformation process, and examine its socio-economic impacts on the traders. This research employs the historical research method, which consists of four stages: heuristics, source criticism, interpretation, and historiography. The findings indicate that the transformation of Wonokromo Market into Darmo Trade Center (DTC) was driven by the government's and the management's efforts to improve trading facilities and accommodate the demands of increasingly modern urban economic development. The transformation brought significant changes to the trading environment and required traders to adapt to new business conditions and market systems.